Survey of the fish fauna of the water bodies of the city of Kharkiv - Honcharov, H.; Vasenko, O.; Turaziani, H. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2023)
The study of the biodiversity of urbanized landscapes, in the context of their permanent expansion, is becoming increasingly important as part of environmental management. The proposed review considers the history of the study and the results of modern research on the ichthyofauna of water bodies in and around the city of Kharkiv. The study includes data obtained during archeological excavations. The existing water fund is estimated as a habitat for fish in the city. We compiled a modern systematic list of the fish fauna, determined its place in the general zoogeographical zonation of the Palearctic, and analyzed the ecological and faunistic characteristics of the fish assemblages, which created a basis for a general assessment of the current state and prospects for changes in the fish community within the city. The state of recreational fishing in the waters of Kharkiv as the main type of utilization of fish resources on its territory is analyzed. The current fish fauna of the water bodies of Kharkiv and its environs consists of 32 species belonging to 31 genera, 11 families, 7 orders, and 4 superorders of bony fish, as well as one hybrid form of silver and bighead carps, whose abundance is maintained only by artificial introduction into water bodies outside Kharkiv with subsequent occasional migration to the city, and two diploid-polyploid hybridogenic complexes of fish of the genera Carassius and Cobitis, whose reproductive characteristics require further study. Five species have disappeared from the local fish fauna, i.e. four species of bony fish (common crucian carp Carassius carassius, Black Sea roach Rutilus frisii, asp Leuciscus aspius, Danilevsky’s dace Leuciscus danilewskii) and the Ukrainian lamprey Eudontomyzon mariae, which used to live in the city or water bodies and watercourses of the adjacent territories. Thirteen fish species (41% of the total species composition) have a conservation status and require special measures for their protection according to national and international regulations. The share of non-native species in the ichthyofauna of Kharkiv is quite significant – eight species (22% of the total number of registered species and forms). The fish fauna of the city is dominated by freshwater fishes, limnophilic or indifferent to the current speed, with phytophilic or psammolithophilic portion spring and summer spawning, not belonging to any particular habitat.